Studies on the Haematinic Potentials of Mucuna pruriens in Mice - Ahmadu, Peter Uchogu; Fidelis, Solomon Ameh; Daburi, Aisha; Onah, Emmanuel; Okhale, Samuel Ehiabhi; Samali, Ayuba; Lawal, Ibrahim; John-Africa, Lucy Binda (British Journal of Healthcare and Medical Research, 2024)
Background: Ethnopharmacological study of Mucuna pruriens, a creeping and leguminous plant used in the treatment of anaemia in the eastern part of Kogi State, Nigeria was carried out. The aim was to evaluate the effect of aqueous extract of the leaves of M. pruriens on haematinic activities in mice. Method: Leaves of M. pruriens was extracted by maceration in water. Phenyl hydrazine 4 mg/kg was administered for four days. Mice were grouped and treated with normal saline 10 ml/kg (normal and anemic control), M. pruriens (100, 200 and 400 mg/kg) and Fersolate (0.0214 mg/kg) p.o for 7 days. Hematological parameters measurements were carried out before treatments, days 1, 7, 14 and 21. The red blood cell count (RBC), haemoglobin concentration (Hb), white blood cell count (WBC) and hematocrit (HCT) were analyzed as indices of anemia. Phytochemical fingerprint using HPLC chromatography and mineral contents were also carried out. Results: Plant extraction percentage yield was 15%. M. pruriens (aq) significantly (p<0.01) produced a 61% recovery from anemia at 400 mg/kg after 7 days of treatment and between 94 to 146.52 % 1 and 2 weeks after treatment at all test doses. Hb, and HCT levels also significantly increased especially at 100 and 200 mg/kg doses of M. pruriens compared to the anemic control both at 1 and 2 weeks after treatment. HPLC analysis showed the presence of alkaloids, glycosides, saponin, terpernoids, carbohydrates, chlorogenic acid, caaffeic acid, rutin, ferulic acid and resins. The extract also contained substantial amounts of vitamins B6, C and E, as well as folic acid and iron. Conclusion: These results provide some evidence to support the traditional use of M. pruriens leaves in the treatment of anaemia.